Contemporary decision-making of mid-size city in the Czech Republic using Multiple Criteria Decision-making - Meaza Birhane Haile; Martin Mastalka (European Journal of Government and Economics (EJGE), 2018)
The strategic planning process has been implemented into the local governance environment in the Czech Republic during last two decades. But the strategic goals that are expressed in the strategic development documents on the local level are only the part of the issues that are to be fulfilled or solved~by the local government. In the everyday practical governance there is always a list of projects that appear from the actual technological, technical, public or political demand. The contemporary decision-making process is based on the personal or collective political decision or on the actual technical demand. But there are also municipalities that are already implementing strategic planning and want to avoid unsystematic interventions and decision-making processes. They try to adopt some attitudes from the corporate sphere to make the decision-making process more open and clear. This paper deals with the methodology of the mid-size city and tries to discuss it and offer some improvements. The paper's other goals are to offer comparison of typical projects that could be found on the local level and to make a model of results provided by the different methodologies used for the decision-making process, specifically weighted sum average and analytic hierarchy process.
Keywords: 330; Analytic hierarchy process; consistency index; public sector; Saaty Matrix; Spearman's correlation; Strategic planning; Weighted Sum Method